Aberrant endothelial expression of hnRNPC1/C2 and VDR and reduced maternal vitamin D levels in women with preeclampsia. Issue 222 (September 2022) - Gu, Yang; Lin, Shuai; Morgan, John A.; Lewis, David F.; Wang, Yuping
Abstract: Vitamin D deficiency is a widespread health problem globally and vitamin D deficiency/ insufficiency in pregnancy is a risk factor for preeclampsia, a hypertensive disorder in human pregnancy. Vitamin D elicits its biological effects through binding to its receptor VDR. In the present study, we determined maternal vascular expression of VDR and hnRNPC1/C2, a native repressor of VDR, in subcutaneous adipose tissue from women with normal pregnancy and preeclampsia. Maternal antenatal and postnatal vitamin D levels were measured. We found that hnRNPC1/C2 expression was markedly increased, while VDR expression was markedly reduced, in maternal vessel endothelium and smooth muscle cells from women with preeclampsia compared to that from normal pregnant controls. Reduced VDR expression was relevant to low maternal antenatal and postnatal vitamin D levels in women with preeclampsia. Using human umbilical vein endothelial cells (HUVECs) as an endothelial model, we further investigated the role of hnRNPC1/C2-mediated VDR expression in endothelial cells, and tested effect of hnRNPC1/C2 inhibition on endothelial response to bioactive vitamin D, 1, 25(OH)2 D3 . Our results showed that inhibition of hnRNPC1/C2 by hnRNPC1/C2 siRNA resulted in not only an increase in endothelial VDR expression, but further improved endothelial response to 1, 25(OH)2 D3 . These findings indicate that aberrant hnRNPC1/C2 expression may contribute to reduced vascular expression of VDR in women with preeclampsia and suggest that hnRNPC1/C2 could be a target for improving vascular endothelial cell response to vitamin D. Highlights: Increased hnNRPC1/C2 expression is associated with reduced VDR expression in maternal vessels in women with preeclampsia. Low maternal vitamin D levels is associated with reduced VDR expression in maternal vessel endothelium in preeclampsia. Inhibition of hnNRPC1/C2 expression results in upregulation of VDR expression in endothelial cells. Inhibition of hnNRPC1/C2 expression promotes endothelial response to vitamin D.